2011
DOI: 10.1039/c1jm10270b
|View full text |Cite
|
Sign up to set email alerts
|

Spacious and mechanically flexible mesoporous silica thin film composed of an open network of interlinked nanoslabs

Abstract: Transparent and smooth silica thin films with a very high porosity were prepared by linking zeolitic nanoslabs into open mesoporous networks. Calcined films characterized by ellipsometric porosimetry presented pore sizes in the range of 6-18 nm and porosities of 70-90% depending on the temperature of assembly of the nanoslabs in the presence of Pluronic P123 triblock copolymer. The films were disordered according to grazing incidence small angle X-ray scattering and transmission electron microscopy. The most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…66 Ellipsometric porosimetry measurements showed that the silica lm had a thickness of 150 nm, a porosity of 55% and a surface area of ca. large area nanostructured substrates for sensing or catalytic applications, the conformal nature of the novel PE-ALD process was veried.…”
Section: Properties Of the Gallium Oxide Lmsmentioning
confidence: 99%
“…66 Ellipsometric porosimetry measurements showed that the silica lm had a thickness of 150 nm, a porosity of 55% and a surface area of ca. large area nanostructured substrates for sensing or catalytic applications, the conformal nature of the novel PE-ALD process was veried.…”
Section: Properties Of the Gallium Oxide Lmsmentioning
confidence: 99%
“…Flexibility is a desired property for all the materials dealing with expansion due to heat, swelling due to lithium uptake, or bendable electronics, however it is specific for organic materials. A material can be classified as mechanically flexible if it exhibits a Young's modulus value below 1 GPa . In general, ceramic materials or classical semiconductors are typically rigid and brittle.…”
mentioning
confidence: 99%
“…While the possibility for tailoring the pore size and the composition of the pore wall opens excltmg opportunities in the fields of catalysis and molecular filtration, the penetration of ALD layers inside nanoporous low-k materials is typically perceived as a disadvantage within the micro-electronics community. In our recent work [4][5][6][7][8][9][10], in-situ XRF was used to quantify the penetration of ALD in nanoporous thin films. In [10], nanoporous SiCOH low-k films with a porosity of � 45% and interconnected pores with a diameters of � 3 nm.…”
Section: Resultsmentioning
confidence: 99%